New case of secondary bladder amyloidosis with massive hematuria—role of intravesical instillations with dimethyl sulfoxide - García Rojo, Esther (Transl Androl Urol, 2019)
Secondary bladder amyloidosis is a rare condition with less than 60 cases published in the world. It is usually secondary to chronic inflammatory processes such as rheumatologic diseases. Hematuria is its predominant and most important symptom, and usually occurs after a bladder catheterization. The diagnostic confirmation is made through a pathological and immunohistochemical study. The treatment must be staggered from less to more invasive. Our objectives are to present a new case of secondary bladder amyloidosis in a woman with a history of chronic bronchiectasis after tuberculosis and frequent super infections, whose main manifestation was a massive hematuria, and review this rare pathology. We have obtained very good initial results using intravesical instillations with dimethyl sulfoxide (DMSO) with complete resolution of the hematuria, the patient remaining asymptomatic for 6 months. After that, there was a recurrence of the hematuria that was treated with embolization of the hypogastric arteries, with good results. We can conclude that, despite being a rare condition, we must consider secondary bladder amyloidosis in patients who have already been diagnosed with systemic amyloidosis and/or chronic pathologies who develop hematuria after bladder catheterization. Based on our experience, instillations with dimethyl sulfoxide are a safe option and provide a quick and temporary resolution of hematuria symptoms.